WLAN SENSING FRAME EXCHANGE PROTOCOL (2022)
Embodiments of a WLAN sensing frame exchange protocol are generally described herein. In some embodiments, a wireless communication device is configured to perform a WLAN sensing protocol within a basic service set (BSS) comprising one or more stations (STAs) (STA1 and STA2) including an access point station (AP STA). The WLAN sensing protocol comprises a discovery phase, a negotiation phase, a measurement phase, and a reporting phase. To perform the WLAN sensing protocol, the wireless communication device is configured to operate as either a sensing initiator or a sensing responder, and to operate as a sensing transmitter and/or a sensing receiver. Some 60 GHz embodiments relate to WLAN sensing in a PBSS or IBSS with DMG STAs.